Synthesis and characterization of green thermoplastic composite from renewable resources - A.S, Auwal; S. M, Gumel; U.G, Bashir; A., Umar; A.A, Bawa; L. A, Jibril (Faculty of Applied Sciences, 2025)
Due to concerns regarding poor degradability and the potential for environmental contamination, the utilization of petrochemical-based plastics should be actively discouraged, leading to a shift toward the adoption of biobased plastics derived from natural sources. Biobased plastics, sourced from renewable materials, are characterized by their elevated costs, biodegradability, compost ability, non-toxicity, and minimal environmental impact. This study investigates the potential of utilizing potato waste starch in the production of bioplastics specifically for packaging applications. In this research, the polymer matrix derived from potato waste was modified with chitosan to enhance its antimicrobial, antifungal, and antiviral properties. Such modifications are expected to significantly improve the biocompatibility, bio adhesiveness, and non-toxicity of the potato waste polymer. Consequently, a modified polymer matrix known as chitosan-modified polylactic acid plastics was synthesized. To further augment the mechanical properties of these bioplastics, a jute fiber reinforcement was incorporated into the polymer matrix. The characterization of the bioplastics was conducted using Fourier-transformed infrared spectroscopy (FTIR), while the tensile properties of the plastic composites were evaluated through tensile testing procedures. The findings indicated that the tensile strength of the composites exhibited an increase in correlation with the concentration of the modifier. Conversely, a significant reduction in elongation at break was observed as the concentration of the modifier increased, highlighting the trade-off between strength and flexibility in the modified bioplastics.